Carotid artery stenting: an update. (November 2019) - Spiliopoulos, Stavros; Vasiniotis Kamarinos, Nikiforos; Reppas, Lazaros; Palialexis, Konstantinos; Brountzos, Elias
Abstract : Purpose of review: To present the latest evidence about carotid artery stenting (CAS) including indications, safety, efficacy, and available equipment. Recent findings: The micromesh stent, a new stent design which offers excellent flexibility and embolic protection, has been associated with promising outcomes. Summary: CAS has emerged as a minimally invasive treatment method for carotid artery stenosis with comparable outcomes with surgical management. The implementation of new technology combined with operator experience has led to a paradigm shift; however, to date, no robust evidence exists about patient and lesion selection. Many studies are underway to clarify the technical aspects of CAS as well as the optimal treatment of carotid artery stenosis for each patient population.